Contractually stable networks - Vincent Vannetelbosch; Jean-François Caulier; Ana Mauleon (Fondazione Eni Enrico Mattei (FEEM), 2009)
We develop a theoretical framework that allows us to study which bilateral links and coalition structures are going to emerge at equilibrium. We define the notion of coalitional network to represent a network and a coalition structure, where the network specifies the nature of the relationship each individual has with his coalition members and with individuals outside his coalition. To predict the coalitional networks that are going to emerge at equilibrium we propose the concept of contractual stability which requires that any change made to the coalitional network needs the consent of both the deviating players and their original coalition partners. We show that there always exists a contractually stable coalitional network under the simple majority decision rule and the component-wise egalitarian or majoritarian allocation rules. Moreover, requiring the consent of group members may help to reconcile stability and efficiency.
Keywords: A14; C70; 330; Networks; Coalition Structures; Contractual Stability; Allocation Rules